2016
DOI: 10.1002/slct.201600111
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot, Clean Synthesis of Vanillic Acid from Ferulic Acid

Abstract: Ferulic acid dissolved in water is selectively oxidized to vanillic acid in high yield ( % 60 %) under remarkably mild and green conditions, namely at room temperature with air as primary oxidant, over a catalytic amount of nanostructured Bi 2 WO 6 . The process is general and opens the route to the selective oxidation of natural substances into derivatives of significant applicative relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
(13 reference statements)
2
13
0
Order By: Relevance
“…443 Similarly, oxidation of trans-ferulic acid embodies a complementary route to vanillin. [635][636][637] Vanillin possesses the potential to serve as a versatile platform chemical, provided that cheap vanillin will become available from future biorefineries in large quantities, either via upgrading of (iso)eugenol or through oxidative depolymerisation of lignin. Numerous polymer building blocks can be derived from vanillin, as demonstrated by Caillol et al 592,638,639 Possible vanillin transformations include the selective oxidation to vanillic acid, the partial reduction to vanillylalcohol, 640 and the reductive amination towards vanillylamine.…”
Section: Chemocatalytic Upgrading Of Phenolic Compoundsmentioning
confidence: 99%
“…443 Similarly, oxidation of trans-ferulic acid embodies a complementary route to vanillin. [635][636][637] Vanillin possesses the potential to serve as a versatile platform chemical, provided that cheap vanillin will become available from future biorefineries in large quantities, either via upgrading of (iso)eugenol or through oxidative depolymerisation of lignin. Numerous polymer building blocks can be derived from vanillin, as demonstrated by Caillol et al 592,638,639 Possible vanillin transformations include the selective oxidation to vanillic acid, the partial reduction to vanillylalcohol, 640 and the reductive amination towards vanillylamine.…”
Section: Chemocatalytic Upgrading Of Phenolic Compoundsmentioning
confidence: 99%
“…Recently, trans-ferulic acid biotransformation employing Escherichia coli [13] bacteria [14], microbial [1,15], fungal strain [16], enzymes [5,8], etc., has also been studied. Likewise, the use of metal oxide catalysts such as inorganic materials Bi 2 WO 6 [17] or metalorganic frameworks [7,9,10] has been explored, even via photocatalytic conversion using TiO 2 [18,19], as well as WO 3 -loaded TiO 2 [20]. Biological transformations provide good vanillin yields but there are some problems related to the purification steps and the presence of remnant bacteria [13,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Complexity of bioconversion processes limits their use in industrial scale production . Recently Paola et al reported a photo‐catalytic route for aerobic oxidation of trans‐ferulic acid to vanillin over TiO 2 under UV irradiation, whereas Delisi et al described a similar process with higher products selectivity over Bi 2 WO 6 under dark conditions . A three‐step process for vanillin synthesis from p ‐cresol has been reported .…”
Section: Introductionmentioning
confidence: 99%